THE EFFECT OF SELF-EFFICACY OF SHIPPING POLYTECHNIC EDUCATION PERSONNEL IN IMPROVING PERFORMANCE - Yulianto, Andri (LPPM STIE Muhammadiah Bandung, 2024)
The objectives of this research are (1) to analyze how much influence leadership has on the performance of Shipping Polytechnic employees through self-efficacy, (2) analyze how big the influence of organizational learning is on the performance of Shipping Polytechnic employees through self-efficacy, and (3) analyze how big the influence of organizational culture on the performance of Shipping Polytechnic employees through self-efficacy. This research uses a multivariate Structural Equation Model (SEM) technique. The software used to process this data is AMOS 22 and the SPSS program as a descriptive statistical measurement tool. The results of this research are (1) Things that can be paid attention to include one dimension of leadership, namely